2023
DOI: 10.1002/pmrj.13044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between sleep apnea and vestibular symptoms following traumatic brain injury

Abstract: IntroductionTraumatic brain injury (TBI) is a complex health problem in military veterans and service members (V/SM) that often involves comorbid vestibular impairment. Sleep apnea is another comorbidity that may exacerbate, and/or be exacerbated by, vestibular dysfunction.ObjectiveTo examine the relationship between sleep apnea and vestibular complaints in V/SM diagnosed with TBI of any severity.DesignMulticenter cohort study; cross‐sectional sample.SettingIn‐patient TBI rehabilitation units within 5 Veterans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…We read with pleasure the article by Skop et al, 1 titled "Exploring the Relationship Between Sleep Apnea and Vestibular Symptoms following Traumatic Brain Injury" and would like to offer additional commentary regarding selection criteria and survey choice. We hope these perspectives can provide insight into areas that may require further research and improvement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with pleasure the article by Skop et al, 1 titled "Exploring the Relationship Between Sleep Apnea and Vestibular Symptoms following Traumatic Brain Injury" and would like to offer additional commentary regarding selection criteria and survey choice. We hope these perspectives can provide insight into areas that may require further research and improvement.…”
mentioning
confidence: 99%
“…Skop et al 1 selected a sample of veterans/service members registered with the Veterans' Affairs Traumatic Brain Injury Model Systems (VA TBIMS) National Database whose responses were analyzed via a multivariable linear regression model for an association between vestibular dysfunction and sleep apnea with a history of TBI diagnosis. The team concluded that sleep apnea and vestibular dysfunction symptoms were not significantly associated once posttraumatic stress disorder was included in the analysis.…”
mentioning
confidence: 99%